THE EFFECTIVENESS OF USING WHATSAPP MEDIA IN TEACHING VOCABULARY IN HIGH SCHOOL - Annisa Shofa Tsuraya; Silaturahmi Silaturahmi (International Conference on Social and Islamic Studies, 2021)
This research aims at finding out whether there is a significant difference or nor on the students’ vocabulary mastery through WhatsApp media and their response in implementing WhatsApp media to the second-grade student of SMAN 1 Madapangga. The method of this research was a pre-experimental research with one-group pretest-posttest design. There were two variables in this research, where WhatsApp media as the independent variable and students’ vocabulary mastery as the dependent variable. The population of this research was the second-grade student of SMAN 1 Madapangga. The total population were 184 students while the sample of this research were 30 students taken by applying simple random sampling technique. For the instrument, it used test (pre-test and post-test) and questionnare. The collected data was analized using scoring classification; mean score and t-test. The mean score of pre-test was 68.90 with standar deviation 14.45 while the mean score of post-test was 82.33 with standar deviation 5.97. Then the value of t-test was bigger than t-table (3.821>2.100). Therefor, the null hyothesis (H0) was rejected whereas the research hypothesis (H1) was accepted. While for Students’ response in implementing WhatsApp media, it showed that most of them felt that WhatsApp media gave good impact to them such as they felt fun and more actively involved in learning vocabulary through WhatsApp media. Based on the results above, the researcher concludes that WhatsApp media can improve students’ vocabulary mastery and it enhances students’ enthusiasm during learning vocabulary process to the second-grade student of SMAN 1 Madapangga.